Pengembangan Instrumen Penilaian Berbasis Peer Assessment dalam Mengukur Penguasaan Materi dan Minat Belajar Peserta Didik Pada Materi Sistem Pernapasan Manusia Di SMA Imelda, Medan - Daulay, Asni Amelia; Khairuddin, Khairuddin; Khairuna, Khairuna (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to determine whether the peer evaluation tool had an impact on students' mastery of respiratory system material and learning interest at SMA Imelda Medan. This is an R&D (research and development) initiative. Development studies are a method for creating and validating products. This study uses the 4D model as a development model: (1) an expert validator questionnaire is used as an assessment tool, (2) a material specialist validator, (3) a questionnaire for student responses, and (4) student worksheets. Based on the results of product validation from several experts, it is known that the average validity level of the peer evaluation method's performance appraisal is 4, included in the very valid category with a value of 3.25 M4. application of performance evaluation technique peer review 32 students is 78.12%. Therefore it can be concluded that the LKS on the respiratory system material based on the peer assessment value can be declared practical to use. And also on the effectiveness of students' interest in learning, the results obtained were 2.56 with the highest category being 29 respondents with a percentage of 90.6% then the second selection, namely the medium category of 3 respondents with a percentage of 9.4%.